Effect of the attention deficit/hyperactivity disorder drug atomoxetine on extracellular concentrations of norepinephrine and dopamine in several brain regions of the rat - Swanson, Chad J.; Perry, Kenneth W.; Koch-Krueger, Susanne; Katner, Jason; Svensson, Kjell A.; Bymaster, Frank P. (Neuropharmacology, 2006)
Atomoxetine is a selective inhibitor of norepinephrine transporters and is currently being used in the pharmacotherapy of attention deficit/hyperactivity disorder (ADHD). We have previously shown that atomoxetine increased extracellular (EX) concentrations of norepinephrine and dopamine in prefrontal cortex, but unlike the psychostimulant methylphenidate, did not alter dopamine EX in nucleus accumbens or striatum. Using the in vivo microdialysis technique in rat, we investigated the effects of atomoxetine on norepinephrine EX and dopamine EX concentrations in several other brain regions and also evaluated the role of inhibitory autoreceptors on atomoxetine-induced increases of norepinephrine EX concentrations. Atomoxetine (3 mg/kg i.p.) increased norepinephrine EX robustly in prefrontal cortex, occipital cortex, lateral hypothalamus, dorsal hippocampus and cerebellum, suggesting that norepinephrine EX is increased throughout the brain by atomoxetine. In lateral hypothalamus and occipital cortex where dopamine EX was quantifiable, atomoxetine did not increase dopamine EX concentrations, in contrast to parallel increases of norepinephrine EX and dopamine EX in prefrontal cortex, indicating a unique effect in prefrontal cortex. Administration of the α 2-adrenergic antagonist idazoxan 1 h after atomoxetine resulted in increases in prefrontal cortical norepinephrine efflux greater than either compound alone, indicating an attenuating effect of the adrenergic autoreceptors on norepinephrine efflux.